Evaluasi Kepuasan Pengguna terhadap Sistem Informasi Provisioning Monitor Indihome Dunsanak (SIMIDUN) menggunakan Metode Service Quality - Devi Gusmita (Jurnal Informatika Ekonomi Bisnis, 2020)
Measurement of the quality of information systems is necessary to evaluate the satisfaction of users of the system as a consideration for companies to develop the information system. This research aims to apply and test the Service Quality method to measure the level of user satisfaction with the Indihome Dunsanak Information System Provisioning Monitor (SIMIDUN) to serve as a benchmark for system developers to develop Indihome Dunsanak's Information System Provisioning Minitor. The data used in this study is data about the details of items or indicators contained in the application to be evaluated, by distributing questionnaires to system users. Data processing is done using the Service Quality method, then the data is processed by calculating the perception value and the expected value based on the questionnaire that has been distributed then calculating the gap score to make a cartesian diagram. The results obtained in the evaluation of user satisfaction information system provisioning indihome dunsanak based on Distribution and Percentage of User Perceptions of the information system that 38.47% of SIMIDUN Information System users are satisfied with the performance of the system and only 18.47% of users assess the performance of the SIMIDUN Information System very much. satisfactory, based on the data obtained that the average servqual score is -0.97 means that the score gap between user expectations and what the user feels is negative. This means that the average expectation of new users is fulfilled by SIMIDUN Information System with a score of 0,97.